IMPROVEMENT OF READING SKILLS THROUGH THE GAME’S CRAFTING TECHNIQUES ON GRADE 1 ELEMENTARY SCHOOL - Lilis Komariah; Anugrah Ramadhan Firdaus (COLLASE (Creative of Learning Students Elementary Education), 2018)
This research aims to improve students reading skills through the application of the technique of composing words. This technique is a form of cooperative learning development that has characterized the developing activities thinking through discussion or group work. The subject of research is the grade 1 SDN 070 Pasirluyu, years 2017/2018 lesson. The research approach used is qualitative while the type of research that is a class act (CAR). Data analysis techniques using interactive model analysis technique consist of three components, namely the reductions of data, data and cereal drawdown conclusion. Based on a result of research that has been carried out can be concluded that crafting game techniques can improve the ability to read grade 1 SDN 070 Pasirluyu. It can be seen from the increase in the number of studying thoroughly in the percentage of the initial conditions that only 54% increased to 71% in cycle 1 and reach 92% the end of cycle 2. The total increase in the result of the study is of 46%  yield close to average at this stage of pre-cycle of 58 rose to 71 in cycle 1 and cycle 2 be 87 on. pre-cycle.